Root and Agro-Morphological Traits Performance in Cowpea under Drought Stress - Ricardo Santos; Márcia Carvalho; Eduardo Rosa; Valdemar Carnide; Isaura Castro (Agronomy, 2020)
Drought is responsible for major yield losses in many worldwide crops and is expected to occur more frequently due to climate change. Cowpea, one of the most drought tolerant legumes, stands as a promising crop in the future climatic context. The screening for genotypes well adapted to this constraint is an essential step to improve cowpea production. A collection of 29 cowpea genotypes (Vigna unguiculata L. Walp.) from the Iberian Peninsula and 11 other countries from worldwide regions was grown and submitted to drought stress using pipes with 30 cm (control) and 90 cm (stress) of height in which water was supplied through the bottom. A set of root and agro-morphological parameters were evaluated, including shoot and root dry weight, root:shoot ratio and stem greenness. Overall, results show that under drought stress, plants seem to invest in root development and reduce shoot biomass. Higher root dry weight under drought conditions could be related to a higher drought tolerance in cowpea. Based on the evaluated traits, it was possible to identify genotypes, particularly C47 (Iran), C56 and C11 (Portugal), which might represent promising cowpea genetic resources for improved drought tolerance breeding.